Development of a topical applied functional food formulation: Adlay bran oil nanoemulgel. (January 2020) - Chang, Wen-Chang; Hu, Yin-Ting; Huang, Qingrong; Hsieh, Shu-Chen; Ting, Yuwen
Abstract: Using bioactive ingredient from natural food sources to treat chronic health problems has become an emerging trend. Compare to oral consumption, topical application is still the preferred route for administrating these active food ingredients to skin for direct treatment of dermal diseases. Emulgel, a polymeric emulsion system, possesses the properties of both emulsions and hydrogel. Thus, a polymeric emulsion dosage could encapsulate both hydrophilic and hydrophobic compounds and improves their storage stability and cellular uptake. Extracted from the by-product of adlay processing, adlay bran oil is found to ameliorate many skin related diseases. Through the construction of a pseudo-ternary phase diagram, a formulation that contains 60% water, 28% adlay bran oil, and 12% Tween 80 was selected since it generates nano-droplets while still maintaining a sufficient surface energy for better stability. Two cycles of 1000 bar pressure treatment were required to produce nanoemulsion using high-pressure homogenizer. The addition of Pluronic® F-127 successfully transformed nanoemulsion into nanoemulgel. Depending on the gelator concentration, the sol-gel transition temperature varies from 20 to 30 °C. Apart from nanoemulsion facilitating higher permeation rate, nanoemulgel promoted the accumulation of bioactive component on the skin is a more suitable functional food formulation for topical uses. Graphical abstract: Image 1 Highlights: By-product from adlay processing was used as the functional food ingredient. Nanoemulgel was developed for topical application of adlay bran oil. The production processed was optimized. Skin permeation rate of nanoemulgel was evaluated.